Genomic landscape and tumor mutational features of resected preinvasive to invasive lung adenocarcinoma - Lin, Yangui; Li, Dan; Hui, Hongliang; Miao, Haoran; Luo, Min; Roy, Bhaskar; Chen, Binbin; Zhang, Wei; Shao, Di; Ma, Di; Jie, Yanbing; Qiu, Fan; et al. (Frontiers in Oncology, 2024)
Introduction: Adenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA) are considered pre-invasive forms of lung adenocarcinoma (LUAD) with a 5year recurrence-free survival of 100%. We investigated genomic profiles in early tumorigenesis and distinguish distinguished mutational features of preinvasive to invasive adenocarcinoma (IAC) for early diagnosis.Methods: Molecular information was obtained from a 689-gene panel in the 90 earlystage LUAD Chinese patients using next-generation sequencing. Gene signatures were identified between pathology subtypes, including AIS/MIA (n=31) and IAC (n=59) in this cohort. Mutational and clinicopathological information was also obtained from the Cancer Genome Atlas (TCGA) as a comparison cohort.Results: A higher mutation frequency of TP53, RBM10, MUC1, CSMD, MED1, LRP1B, GLI1, MAP3K, and RYR2 was observed in the IAC than in the AIS/MIA group.The AIS/MIA group showed higher mutation frequencies of ERBB2, BRAF, GRIN2A, and RB1. Comparable mutation rates for mutually exclusive genes (EGFR and KRAS) across cohorts highlight the critical transition to invasive LUAD. Compared with the TCGA cohort, EGFR, KRAS, TP53, and RBM10 were frequently mutated in both cohorts. Despite limited gene mutation overlap between cohorts, we observed variant mutation types in invasive LUAD. Additionally, the tumor mutation burden (TMB) values were significantly lower in the AIS/MIA group than in the IAC group in both the Chinese cohort (P=0.0053) and TCGA cohort (P<0.01).These findings highlight the importance of distinguishing preinvasive from invasive LUAD in the early stages of LUAD and both pathology and molecular features in clinical practice, revealing genomic tumor heterogeneity and population differences.